Inflation Post COVID-19: Are the Concerns Justified? - ZG Überblick (Wirtschaftsdienst)
Abstract In August 2021, the German inflation rate is expected to rise to 3.9 %. Part of this is likely due to one-off effects. In Germany, these include above all the reversal of the VAT cut, the expansion of CO2 pricing and price increases due to the scarcity of raw materials and intermediate products. Nevertheless, there may also be structural reasons for rising inflation. For example, the loose monetary policy and the ECB’s new inflation target are partly to blame for higher inflation risks. In addition, the expansive fiscal policy of the new Biden administration is leading to higher rates of price increases in the US. Other aspects, the possibility of a wage-price spiral and whether inflation is measured correctly at all, will also be discussed in this Zeitgespräch.